EVALUATING THE INFLUENCE OF TRAINING ON PRODUCTIVITY OF MEDICAL SUPPORT STAFF AT PERMATA CIBUBUR HOSPITAL - Ramadhani, Syafira Nur Fajrin; Permana, Iman (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study aims to evaluate the impact of training on the productivity of medical support employees at Permata Cibubur Hospital, addressing the critical role of human resources in achieving organizational objectives and enhancing employee skills. Utilizing a mixed-methods approach, the research combines qualitative interviews and observations with quantitative questionnaires to assess productivity changes before and after training. Data collection includes primary sources (interviews,  observations, questionnaire) and secondary sources (training records and HR reports), ensuring a comprehensive analysis through thematic analysis for qualitative data and descriptive statistics for observational data and also the SPSS analysis used to assess the effectiveness of treatment, marked by a difference in the average before and after the training. The study is expected to reveal that effective training significantly enhances employee skills and knowledge, leading to improved productivity levels among medical support staff. Key productivity indicators such as motivation, job orientation, and interpersonal relationships are anticipated to show positive changes post-training. The research is limited to medical support staff at Permata Cibubur Hospital, which may restrict the generalizability of the findings to other healthcare settings or employee categories. This research contributes to human resource management theory by providing insights into the relationship between training and productivity, emphasizing the need for tailored training programs that align with individual employee needs and organizational goals. The findings will offer valuable insights for hospital management to refine training strategies, ultimately enhancing service quality and operational efficiency, while also addressing performance issues stemming from employee limitations. This study fills a gap in understanding the specific impact of training on productivity levels among medical support staff in the healthcare sector, highlighting the importance of systematic training processes in fostering employee development and organizational competitiveness.